2014
DOI: 10.1016/j.ijdevneu.2014.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Cortex glial cells activation, associated with lowered mechanical thresholds and motor dysfunction, persists into adulthood after neonatal pain

Abstract: We investigated if changes in glial activity in cortical areas that process nociceptive stimuli persisted in adult rats after neonatal injury. Neonatal pain was induced by repetitive needle prickling on the right paw, twice per day for 15 days starting at birth. Wistar rats received either neonatal pain or tactile stimulation and were tested behaviorally for mechanical withdrawal thresholds of the paws and gait alterations, after 15 (P15) or 180 (P180) days of life. Brains from rats on P15 and P180 were immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The sensitive period in regard to long‐term alterations in nociceptive responses is limited to the first 7–10 days of life in the rat (Ren et al, 2005). However the detection of a more precise age in neonatal rats and the study of the effects of pain and stress interactions in these animals would contribute to a better understanding of this important topic so in this study we used a model with painful stimuli from PND 2 to PND 15 (Sanada et al, 2014; Carmo Ede et al, 2016; Nuseir et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitive period in regard to long‐term alterations in nociceptive responses is limited to the first 7–10 days of life in the rat (Ren et al, 2005). However the detection of a more precise age in neonatal rats and the study of the effects of pain and stress interactions in these animals would contribute to a better understanding of this important topic so in this study we used a model with painful stimuli from PND 2 to PND 15 (Sanada et al, 2014; Carmo Ede et al, 2016; Nuseir et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that the neurogenic effects of early repetitive noxious experiences are limited to PND 1 (postnatal day 1) and PND 8 (Malheiros et al, 2014; Amaral et al, 2015; den Hoogen et al, 2017) and that repetitive stimulation of the nociceptive system in a rat model using needle pricks in the hind‐paw closely mimics the clinical situation of infants in NICU (den Hoogen et al, 2017). In contrast, repeated procedural pain during the first 14–15 days of life in rat pups resulted in impairment of long‐term memory (Nuseir et al, 2017) and sensory and motor functions (Sanada et al, 2014; Carmo Ede et al, 2016). In fact, rat pups are born premature and the first week of their lives corresponds to gestation weeks 24–36 in human babies (Anand et al, 1999; Andreollo et al, 2012; Dutta and Sengupta, 2016) while week two corresponds to newborn human babies (Sengupta, 2013), so we chose to study the effect of painful stimuli during the first 15 days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Painful stimuli in the neonatal period produces pain behaviors immediately after injury that persist into adult life, and is accompanied by an increase in glial activation in cortical areas that process or interpret pain. These results suggest a role of glial cells in the PFC, in the chronification of pain [ 200 ].…”
Section: Changes In the Pfc During Chronic Painmentioning
confidence: 99%
“…The American Veterinary Medical Association (AVMA) has stated that “animal pain and suffering are clinically important conditions that adversely affect an animal's quality of life” (American Veterinary Medical Association, ). In addition to the negative impact that occurs at the time of the painful insult, untreated pain in both human and animal neonates may cause hypersensitivity to subsequent painful procedures (McCracken, Waran, Mitchinson, & Johnson, ; Page, ; Taddio, Goldbach, Ipp, Stevens, & Koren, ; Taddio, Katz, Ilersich, & Koren, ) and an increased propensity for long‐term pain (Hermann, Hohmeister, Demirakca, Zohsel, & Flor, ; Miranda et al., ; Page, ; Ren et al., ; Sanada et al., ; Walker, Tochiki, & Fitzgerald, ). These nociceptive responses can be alleviated with the appropriate use of analgesia during the initial painful stimulus (Page, ; Taddio et al., ).…”
Section: Introductionmentioning
confidence: 99%